Sea lions as a natural model for charting the developmental course following in utero exposure to domoic acid - Peter F. Cook; Colleen Reichmuth; Megan E. Moriarty; Alissa C. Deming; Vanessa Fravel Hoard; Cara Field; Frances Gulland (Harmful Algae, 2026)

Sydney’s first terrestrial gamma-radiation map - Tengiz Ibrayev; Matilda Lawton; Giancarlo Ciotoli; Osama Fawwaz; Artem Knyazev; Blake Orr; Megan Cook; Laura Manenti (Journal of Environmental Radioactivity, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

MLH1 c.27G>A (p.Arg9=) is a synonymous likely/pathogenic variant underlying variably mosaic constitutional MLH1 methylation in Lynch syndrome - Rocio Alvarez; Paula Climent-Cantó; GiWon Shin; Francesca Paola Aguirre; Lisa Zhou; Dennis J. Hazelett; Brent K. Larson; Covadonga Vara; Gabriel Capellá; Víctor Lorca Castellanos; Pilar Garre Rubio; Françoise Desseigne; et al. (Familial Cancer, 2025)

Prenatal per- and polyfluoroalkyl substance mixtures and weight for length from birth to 12 months: The New Hampshire Birth Cohort Study - Gyeyoon Yim; Caitlin G. Howe; Lisa G. Gallagher; Diane Gilbert-Diamond; Antonia M. Calafat; Julianne Cook Botelho; Margaret R. Karagas; Megan E. Romano (Science of The Total Environment, 2025)

Prenatal per- and polyfluoroalkyl substances and blood pressure trajectories in the New Hampshire Birth Cohort Study - Yuting Wang; Elizabeth C. Anderson; Caitlin G. Howe; Jiang Gui; Lisa G. Gallagher; Brianna Heggeseth; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas; Megan E. Romano (International Journal of Hygiene and Environmental Health, 2025)

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Microplastic pollution in salt marsh and urban tributary sediment cores of the River Thames estuary, UK: Spatial and temporal accumulation trends - Megan M. Trusler; Sarah Cook; Barry H. Lomax; Christopher H. Vane (Marine Pollution Bulletin, 2025)

Microplastics pollution in sediments of the Thames and Medway estuaries, UK: Organic matter associations and predominance of polyethylene - Megan M. Trusler; Vicky L. Moss-Hayes; Sarah Cook; Barry H. Lomax; Christopher H. Vane (Marine Pollution Bulletin, 2024)

Investigation of the distribution of transuranic radionuclides in marine sediment at the Montebello Islands, Western Australia - Madison Williams-Hoffman; Megan Cook; Jack K. Clegg; Ross Kleinschmidt; Pere Masqué; Mathew P. Johansen (Journal of Environmental Radioactivity, 2024)

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

Plasma per- and polyfluoroalkyl substance mixtures during pregnancy and duration of breastfeeding in the New Hampshire birth cohort study - Megan E. Romano; Lisa G. Gallagher; George Price; Kathryn A. Crawford; Rachel Criswell; Emily Baker; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas (International Journal of Hygiene and Environmental Health, 2024)

Spatial variation in spawning timing for multi-species Acropora assemblages in the Red Sea - Eslam O. Osman; David J. Suggett; Tamer M. Attalla; Marco Casartelli; Nathan Cook; Islam El-Sadek; Ahmed Gallab; Elizabeth A. Goergen; Neus Garcias-Bonet; Jessica S. Glanz; Pedro Henrique Pereira; Megan Ramirez-Sanchez; et al. (Frontiers in Marine Science, 2024)
Sexual reproduction is a crucial process for reef building coral populations to maximize genetic diversity and recover from large scale disturbances. Mass spawning events by Acropora species represent critical opportunities for populations to persist, and a process that is increasingly exploited to actively restore degraded reefs. However, the timing and predictive capacity of coral spawning throughout the broad thermal and environmental regime of the Red Sea – a region also undergoing significant development and active reef restoration – remains patchy. We, therefore, conducted three parallel reef surveys in the central Red Sea (Al-Fahal Reef, Thuwal - Saudi Arabia) and the eastern (Shushah Island - Saudi Arabia) and western (Hurghada – Egypt) coast of the northern Red Sea. Surveys assessed the gravidity of gonads, spawning timing, alignment with the lunar cycle of 21 Acropora spp. (total n= 572 colonies) around the full moons of April and May 2023. Consistent with past observations, synchronous spawning was observed for Acropora spp. in both the central and northern Red Sea during April and May, respectively. Interestingly, corals spawned on the full moon in both Shushah and Thuwal sites. In contrast, corals in Hurghada were independent of the lunar cycle and spawned 7-9 nights before the full moon in May. By integrating our 2023 observations with the historical spawning events in Hurghada and Thuwal (2002-2022), we found that the deviation of spawning timing from the full moon day was correlated with absolute Sea Surface Temperature (SST) (earlier spawning before the full moon day, lower SST) and warming rate (earlier spawning, more rapid warming) in 6-weeks prior to spawning. As such, temperature pattern is likely one of the primary factors governing gamete release, among other factors, that likely influence spawning day within the lunar month. These correlations between SST metrics and spawning timing suggest a potential framework to predict future Acropora spp. spawning dates. Our observations demonstrate the importance of parallel efforts across borders to collect critical data needed to inform management strategies aimed at conserving and restoring coral reefs in this ecologically diverse region.

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

Development and Validation of an Abbreviated Child and Adult Food Security Scale for Use in Clinical and Research Settings in the United States - Ana Poblacion; Stephanie Ettinger de Cuba; Deborah A. Frank; Georgiana Esteves; Lindsey J. Rateau; Timothy C. Heeren; Sharon Coleman; Maureen M. Black; Diana B. Cutts; Félice Lê-Scherban; Eduardo R. Ochoa; Megan Sandel; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

X-ray computed tomography: A novel non-invasive approach for the detection of microplastics in sediments? - Megan M. Trusler; Craig J. Sturrock; Christopher H. Vane; Sarah Cook; Barry H. Lomax (Marine Pollution Bulletin, 2023)

Metals and per- and polyfluoroalkyl substances mixtures and birth outcomes in the New Hampshire Birth Cohort Study: Beyond single-class mixture approaches - Gyeyoon Yim; Glen McGee; Lisa Gallagher; Emily Baker; Brian P. Jackson; Antonia M. Calafat; Julianne Cook Botelho; Diane Gilbert-Diamond; Margaret R. Karagas; Megan E. Romano; Caitlin G. Howe (Chemosphere, 2023)

Sandy beach dynamics by constrained wave energy minimization - Ronan Dupont; Megan Cook; Frédéric Bouchette; Bijan Mohammadi; Samuel Meulé (Ocean Modelling, 2023)

Microbial diversity in stingless bee gut is linked to host wing size and influenced by the environment - Hongwei Liu; Mark A. Hall; Laura E. Brettell; Juntao Wang; Megan Halcroft; Scott Nacko; Robert Spooner-Hart; James M. Cook; Markus Riegler; Brajesh K. Singh (Journal of Invertebrate Pathology, 2023)

Novel Application of Photogrammetry to Quantify Fascicle Orientations of Female Cadaveric Pelvic Floor Muscles - Megan R. Routzong; Mark S. Cook; William Barone; Steven D. Abramowitch; Marianna Alperin (Annals of Biomedical Engineering, 2021)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Analysis of recombinant inbred line populations derived from wheat landraces to identify new genes for wheat stem sawfly resistance - Andrea C. Varella; David K. Weaver; Nancy K. Blake; Megan L. Hofland; Hwa-Young Heo; Jason P. Cook; Peggy F. Lamb; Katherine W. Jordan; Eduard Akhunov; Shiaoman Chao; Luther E. Talbert (Theoretical and Applied Genetics, 2019)

Using social‐network research to improve outcomes in natural resource management - Julie E. Groce; Megan A. Farrelly; Bradley S. Jorgensen; Carly N. Cook (Conservation Biology, 2019)
The conservation and management of natural resources operates in social–ecological systems in which resource users are embedded in social and environmental contexts that influence their management decisions. Characterizing social networks of resource users can be used to inform understanding of social influences on decision making, and social network analysis (SNA) has emerged as a useful technique to explore these relationships. We synthesized how SNA has been used in 85 studies of natural resource management. We considered how social networks and social processes (e.g., interactions between individuals) influence each other and in turn influence social outcomes (e.g., decisions or actions) that affect environmental outcomes (e.g., improved condition). Descriptive methods were used in 58% of the studies to characterize social processes, and 42% of the studies compared multiple networks or multiple points in time to assess social or environmental outcomes. In 4 studies, authors assessed network interventions intended to affect social processes or environmental outcomes. The heterogeneity in case studies, methods, and analyses preclude general lessons. Thus, to structure and further learning about the role of social networks in achieving environmental outcomes, we created a typology that deconstructs social processes, social outcomes, and environmental outcomes into themes and options of social and ecological measures within each. We suggest shifts in research foci toward intervention studies to aid in understanding causality and inform the design of conservation initiatives. There is a need to develop clearer justification and guidance around the proliferation of network measures. The use of SNA in natural resource management is expanding rapidly; thus, now is the time for the conservation community to build a more rigorous evidence base to demonstrate the extent to which social networks can play a role in achieving desired social and environmental outcomes.

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Characterization of resistance to the wheat stem sawfly in spring wheat landrace accessions from targeted geographic regions of the world - Andrea C. Varella; David K. Weaver; Jason P. Cook; Nancy K. Blake; Megan L. Hofland; Peggy F. Lamb; Luther E. Talbert (Euphytica, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Participant understanding and recall of informed consent for induced pluripotent stem cell biobanking - Tristan McCaughey; Christine Y. Chen; Elisabeth De Smit; Gwyneth Rees; Eva Fenwick; Lisa S. Kearns; David A. Mackey; Casimir MacGregor; Megan Munsie; Anthony L. Cook; Alice Pébay; Alex W. Hewitt (Cell and Tissue Banking, 2016)

GidA Expression in Salmonella is Modulated Under Certain Environmental Conditions - Jaclyn M. Rehl; Daniel C. Shippy; Nicholas M. Eakley; Megan D. Brevik; Jordan M. Sand; Mark E. Cook; Amin A. Fadl (Current Microbiology, 2013)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Synthesis of Upper Mississippi River System submersed and emergent aquatic vegetation: past, present, and future - Megan Moore; Susan P. Romano; Thad Cook (Hydrobiologia, 2010)